N'Dama cattle - a productive trypanotolerant breed - Starkey, P.H. (1984)
The N'Dama is a West African breed noted for its size and its trypanotolerance. It is considered to be a bos taurus breed, derived from the Hamitic longhorn ancestral type. N'Dama cattle are mostly kept under traditional management conditions and poor environments, in such circumstances their survival ability and performance are particularly important. They respond well to improved management, improved pastures and reduced trypanosomiasis risk, and can maintain levels of productivity comparable with other African beef breeds. The N'Dama deserves significant attention in national breeding programs in west, central and possibly eastern Africa, as a productive and trypanotolerant breed.